The Evolution Of Children's Creativity In The Age Of The Millennium - Jailani, M. Syahran; Vitaloka, Wulansari; Supriadi, Supriadi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
This paper will examine the evolution of children's creativity in the new millennium. The world of children is full of surprises, and the world of play is abundant with the sparks of a child's imagination in expressions that are so genuine, spontaneous, and astonishing. Children's imagination develops concurrently with their cognitive and linguistic abilities. And serve as a method for children to comprehend the reality of their existence and their surroundings. This study employs a descriptive qualitative methodology, which, in addition to utilizing available literature, makes observations on the research object. Creativity is the capacity to conceive of things in novel and uncommon ways and to generate original solutions to children's issues. Children who are creative are insatiably inquisitive, have many interests, and are enthusiastic about their hobbies and activities. The answer to a child's curiosity is creativity. Today's children have an abundance of potential due to their creativity.